1990
DOI: 10.1016/s0006-3495(90)82349-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanisms of electric field-induced DNA transfection. I. DNA entry by surface binding and diffusion through membrane pores

Abstract: A study of mechanisms of electrotransfection using Escherichia coli (JM 105) and the plasmid DNA pBR322 as model system is reported. pBR322 DNA carries an ampicillin resistance gene: E. coli transformants are conveniently assayed by counting colonies in a selection medium containing 50 micrograms/ml ampicillin and 25 micrograms/ml streptomycin. Samples not exposed to the electric field showed no transfection. In the absence of added cations, the plasmid DNA remains in solution and the efficiency of the transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 29 publications
2
55
0
Order By: Relevance
“…Based on comparison with five studies, correlation predictions of peak transfection conditions in vivo [39][40][41][42][43] were of similar accuracy as for cell suspensions (MAPE = 51 ± 53%), which suggests that this correlation may be of importance in developing clinical applications. Predictions of peak transfection conditions for bacteria and yeast 22, [44][45][46][47][48] (MAPE = 48 ± 62%) were not as good as for mammalian cells, but predictions of 50% viability conditions were similarly accurate (MAPE = 21 ± 8%) (eg Figure 2d).…”
Section: Mammalian Viability Predictionsmentioning
confidence: 71%
“…Based on comparison with five studies, correlation predictions of peak transfection conditions in vivo [39][40][41][42][43] were of similar accuracy as for cell suspensions (MAPE = 51 ± 53%), which suggests that this correlation may be of importance in developing clinical applications. Predictions of peak transfection conditions for bacteria and yeast 22, [44][45][46][47][48] (MAPE = 48 ± 62%) were not as good as for mammalian cells, but predictions of 50% viability conditions were similarly accurate (MAPE = 21 ± 8%) (eg Figure 2d).…”
Section: Mammalian Viability Predictionsmentioning
confidence: 71%
“…Electroporation facilitates transfer of chemicals or plasmid DNA from extracellular milieu into cells by increasing the permeability of the cell membrane. 13,14 This method of The effect on tumor growth of the order in which the two genes were administered is shown. The group in which the angiostatin gene was transferred followed by the endostatin gene (1 week later) showed no inhibition on the tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…This method is more efficient than transfer using nonviral vectors. [12][13][14] Although there have been several reports of electroporation used in vivo to transfer therapeutic genes, 15,16 usually by applying high-voltage direct current electric pulses to cells in vitro or tissues in vivo, a lower level of electric power is desirable in a clinical setting. 17 In recent study, we showed that low-voltage electroporation combined with chemotherapy has been effective against antitumor growth and also convenient in clinical use.…”
mentioning
confidence: 99%
“…Electrically induced pores shrink in size in milliseconds but reseal in minutes to hours (36,44). Conflicting data on detection of PEF-induced cell injury were reported in other studies.…”
mentioning
confidence: 85%